2021
DOI: 10.3389/fbioe.2021.721581
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Stem Cell Differentiation by Inorganic Nanomaterials: Recent Advances in Regenerative Medicine

Abstract: Transplanting stem cells with the abilities of self-renewal and differentiation is one of the most effective ways to treat many diseases. In order to optimize the therapeutic effect of stem cell transplantation, it is necessary to intervene in stem cell differentiation. Inorganic nanomaterials (NMs), due to their unique physical and chemical properties, can affect the adhesion, migration, proliferation and differentiation of stem cells. In addition, inorganic NMs have huge specific surface area and modifiabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Several groups reported the increased osteogenic potential of bone marrow mesenchymal stem cells (BMSCs) loaded with MNPs [ 36 , 37 ]. Adipogenesis and increased osteogenesis were previously reported in ADSCs incorporating MNPs [ 27 , 38 ], a process that appears to, however, decrease with increasing concentrations of MNPs [ 39 , 40 ]. Herein, we found that both 63.5 as well as 125 μg/mL MNP-CA-PCA support ADSC adipogenesis and osteogenesis in vitro in the experimental conditions created.…”
Section: Discussionmentioning
confidence: 92%
“…Several groups reported the increased osteogenic potential of bone marrow mesenchymal stem cells (BMSCs) loaded with MNPs [ 36 , 37 ]. Adipogenesis and increased osteogenesis were previously reported in ADSCs incorporating MNPs [ 27 , 38 ], a process that appears to, however, decrease with increasing concentrations of MNPs [ 39 , 40 ]. Herein, we found that both 63.5 as well as 125 μg/mL MNP-CA-PCA support ADSC adipogenesis and osteogenesis in vitro in the experimental conditions created.…”
Section: Discussionmentioning
confidence: 92%
“…Remarkable developments in nanotechnology for stem cell isolation, preservation, and regulation have been made during the past 10 years. Utilizing nanomaterials and nano 3D designs as a means to regulate stem cells and govern their differentiation, proliferation, and maturation is part of the regulatory process for stem cells 74,75 . In the instance of skin regeneration, stem cells that transiently produce high levels of VEGF and were manipulated in a way that promotes angiogenesis have been generated 76 .…”
Section: Nanoparticle‐based Therapeutic Strategies For Treating Dfusmentioning
confidence: 99%
“…Utilizing nanomaterials and nano 3D designs as a means to regulate stem cells and govern their differentiation, proliferation, and maturation is part of the regulatory process for stem cells. 74,75 In the instance of skin regeneration, stem cells that transiently produce high levels of VEGF and were manipulated in a way that promotes angiogenesis have been generated. 76 Nanotechnology has paved the way for a creative approach that utilizes nonviral nanomaterials to deliver the human VEGF gene to human embryonic stem cell-derived cells (hESdCs) and human mesenchymal stem cells (hMSCs).…”
Section: Using Stem Cells In Dfumentioning
confidence: 99%
“…Using one or two small molecules are not enough to completely change the phenotype of CSCs. In addition to chemical compounds and small molecules, nanomaterials have attracted considerable interest in inducing CSCs differentiation into non‐tumorigenic cancer cells by modulating the tumor microenvironment 14–16 . Studies from regenerative medicine indicated that nanomaterials could either kill or differentiate the CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chemical compounds and small molecules, nanomaterials have attracted considerable interest in inducing CSCs differentiation into non-tumorigenic cancer cells by modulating the tumor microenvironment. [14][15][16] Studies from regenerative medicine indicated that nanomaterials could either kill or differentiate the CSCs. For example, carbon-based nanomaterials such as multi-well carbon nanotubes, 17 metallofullerenes, 18 and graphene oxide 19…”
mentioning
confidence: 99%